1999
DOI: 10.1128/jcm.37.5.1269-1273.1999
|View full text |Cite|
|
Sign up to set email alerts
|

Detection and Species Determination of Malaria Parasites by PCR: Comparison with Microscopy and with ParaSight-F and ICT Malaria Pf Tests in a Clinical Environment

Abstract: A rapid procedure for the diagnosis of malaria infections directly from dried blood spots by PCR amplification was evaluated with samples from 52 patients. Plasmodium infections were identified with a genus-specific primer set, and species differentiation betweenPlasmodium falciparum and Plasmodium vivax was analyzed by multiplex PCR. The PCR test with any of the three primer sets was able to detect as few as four parasites per microliter by gel electrophoresis or by nonisotopic paper hybridization chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(31 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…The two GTTS-negative but MPH-positive cases were con®rmed positive by nested PCR (one mixed Pf±Pv, one Pv only). This supports other PCR-based studies, which also showed that additional malaria cases are detected by PCR among those determined as negative by microscopy or rapid antigen tests (Postigo et al 1998;Rubio et al 1999;Singh et al 1999;Tham et al 1999;Zhong & Kain 1999 1 ). The moderate correlation between parasite densities and absorbance reading, although limited to the parasite density range of 7000/ll and below, suggests that MPH may be a useful semiquantitative tool to monitor treatment outcomes and to predict recrudescence such as suggested by other PCR-based techniques (Kain et al 1994;Ciceron et al 1999).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The two GTTS-negative but MPH-positive cases were con®rmed positive by nested PCR (one mixed Pf±Pv, one Pv only). This supports other PCR-based studies, which also showed that additional malaria cases are detected by PCR among those determined as negative by microscopy or rapid antigen tests (Postigo et al 1998;Rubio et al 1999;Singh et al 1999;Tham et al 1999;Zhong & Kain 1999 1 ). The moderate correlation between parasite densities and absorbance reading, although limited to the parasite density range of 7000/ll and below, suggests that MPH may be a useful semiquantitative tool to monitor treatment outcomes and to predict recrudescence such as suggested by other PCR-based techniques (Kain et al 1994;Ciceron et al 1999).…”
Section: Discussionsupporting
confidence: 85%
“…This study is unique for its relatively high percentage of low-density (£100/ll) parasitaemias (33.0%, 34/103). This explains why sensitivity of MPH was not 100% or approaching 100% as recently reported for other PCR-based techniques (Singh et al 1999;Tham et al 1999;Zhong & Kain 1999). These levels of parasitaemia are the most likely to be missed by routine GTTS or immunochromatographic technique.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…2005) or to parasite density below the microscopy threshold of detection (50–100 parasites/μl) (WHO 1998). Indeed, malaria infection can be detected by PCR in samples negative for microscopy but positive by RDT (Tham et al. 1999; Moody & Chiodini 2002).…”
Section: Prevalences Of Malarial Infection Among the Study Populatiomentioning
confidence: 99%